Dynamic interplay between AfadinS1795 phosphorylation and diet regulates glucose homeostasis in obese mice. (1st September 2021) - Tozzi, Marco; Brown, Erin L.; Petersen, Patricia S. S.; Lundh, Morten; Isidor, Marie S.; Plucińska, Kaja; Nielsen, Thomas S.; Agueda‐Oyarzabal, Marina; Small, Lewin; Treebak, Jonas T.; Emanuelli, Brice
Abstract : Key points: Afadin is a ubiquitously expressed scaffold protein with a recently discovered role in insulin signalling and glucose metabolism. Insulin‐stimulated phosphorylation of Afadin at S1795 occurs in insulin‐responsive tissues such as adipose tissue, muscle, liver, pancreas and heart. Afadin abundance and Afadin S1795 phosphorylation are dynamically regulated in metabolic tissues during diet‐induced obesity progression. Genetic silencing of Afadin S1795 phosphorylation improves glucose homeostasis in the early stages of diet‐induced metabolic dysregulation. Afadin S1795 phosphorylation contributes to the early development of obesity‐related complications in mice. Abstract: Obesity is associated with systemic insulin resistance and numerous metabolic disorders. Yet, the mechanisms underlying impaired insulin action during obesity remain to be fully elucidated. Afadin is a multifunctional scaffold protein with the ability to modulate insulin action through its phosphorylation at S1795 in adipocytes. In the present study, we report that insulin‐stimulated Afadin S1795 phosphorylation is not restricted to adipose tissues, but is a common signalling event in insulin‐responsive tissues including muscle, liver, pancreas and heart. Furthermore, a dynamic regulation of Afadin abundance occurred during diet‐induced obesity progression, while its phosphorylation was progressively attenuated. To investigate the role of Afadin S1795 phosphorylation in the regulation of whole‐body metabolic homeostasis, we generated a phospho‐defective mouse model (Afadin SA) in which the Afadin phosphorylation site was silenced (S1795A) at the whole‐body level using CRISPR‐Cas9‐mediated gene editing. Metabolic characterization of these mice under basal physiological conditions or during a high‐fat diet (HFD) challenge revealed that preventing Afadin S1795 phosphorylation improved insulin sensitivity and glucose tolerance and increased liver glycogen storage in the early stage of diet‐induced metabolic dysregulation, without affecting body weight. Together, our findings reveal that Afadin S1795 phosphorylation in metabolic tissues is critical during obesity progression and contributes to promote systemic insulin resistance and glucose intolerance in the early phase of diet‐induced obesity.